THE “URBAN GEOLOGY” PROJECT OF IGME: THE CASE STUDY OF NAFPLIO, ARGOLIS PREFECTURE, GREECE - Tsombos, P. I; Zervakou, A.D. (Bulletin of the Geological Society of Greece, 2010)
The Institute of Geology and Mineral Exploration of Greece (I.G.M.E.), in the framework of CSF 2000 – 2006 (Community Support Framework 2000-2006), implemented the pilot project “Collection, Codification and Documentation of geothematic information for urban and suburban areas in Greece - pilot applications”. Geological, geochemical, geophysical, geotechnical, hydrogeological and other geothematic data concerning the urban and surrounding areas of Drama (North Greece), Nafplio & Sparti (Peloponnese) and Thrakomakedones (Attica) were collected. Drillings, geological and neotectonic mapping and other “in situ” measurements and field work took place. All initial and derived analogical and digital data were compiled and processed in specially designed geo-databases in GIS Environment. The final results are presented in geothematic maps and other digital products (DEMs, 2D – 3D surfaces, geodatabases). Such data constitute the essential knowledge base for land use planning and environmental protection in specific urban areas. Through this pilot project, new scientific approaches, methodologies and standards were developed and improved in order to apply to other future projects concerning the major cities of the whole country.